Conservative surgery of the breast - Orešić, Vladimir (Radiology and oncology (Ljubljana), 1997)
In this presentation we tried to show the evolution of breast conserving surgery in our Department. The first breast conserving operations were done in1982. In 1986 the number of patients undergoing these procedures started to increase. The break point was the year 1993 when we started our breast cancerscreening program, and since then the number has been increasing rapidly.
Keywords: Breast neoplasms; Mastectomy; Methods; Surgery; Treatment outcome